The Influence of the Cooperative Learning Model Think Pair Share Type Containing Science Literacy on Students Learning Competencies at SMA Negeri 1 Baso - Eka Charisma Maulidia; Rahmadhani Fitri; Sa'diatul Fuadiyah; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2019)
This research was based on the problems that exist in SMA Negeri 1 Baso, students learning competencies are still low. The efforts that can be made were applying the learning model Think Pair Share with science literacy on reproduction system material at SMA Negeri 1 Baso. The purpose of this research was to determine the increase in the students competencies through the model Think Pair Share with science literacy in the material of reproduction system in SMA Negeri 1 Baso. This type of research is experimental research with a randomized control group posttest only design. The population in this study were all class XI MIPA SMA Negeri 1 Baso registered in the 2018/2019. Sampling was done using Purposive Sampling technique, which was chosen as the sample of the research was class XI MIPA 2 as the experimental class and XI MIPA 3 as the control class. The instruments used were in the form of questions posttest for knowledge competency, observation sheets for students attitudes and skills. The hypothesis was tested using the t-test, can be concluded that the competence of learners knowledge (2.1>1.67), competency assessment value (6.17>1.67) and competency skills value (2.9>1.67). This was an accepted hypothesis. It was concluded that the cooperative model of Think Pair Share type with literacy improve the competency of knowledge, attitude, and skill of class XI MIPA students of SMA Negeri 1 Baso.